Efektifitas Layanan Pernikahan Pada Masa Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) Darurat Di Kantor Urusan Agama Kebomas Gresik Perspektif SE. NO : P-001/DJ III/Hk.007/07/2021 - Fashihuddin Arafat; Erina Putri Amalia (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2022)
This study aims to describe the implementation of marriage service policies during the implementation of emergency community activity restrictions (PPKM) at the Office of Religious Affairs, Kebomas District, Gresik Regency, describe the supporting and inhibiting factors, as well as solutions to overcome these obstacles. A qualitative-descriptive approach was used as an analytical knife. The results showed that the policy of marriage services during the implementation of emergency community activity restrictions (PPKM) at the Office of Religious Affairs was stated in Circular No.: P-001/DJ III/Hk.007/07/2021 concerning Technical Guidelines for Marriage Services at KUA District of Emergency PPKM Period. The circular has also been implemented according to the guidelines and is considered effective in its implementation, although there are things that are found to be obstacles, such as there are still people who do not fully comply with the health protocol rules by not wearing masks and not keeping their distance. However, the KUA Kebomas District has taken strategic steps to overcome these obstacles.